Evaluation of Imidazole-Based Compounds as Heme Oxygenase-1 Inhibitors - Sorrenti, Valeria; Guccione, Salvatore; Di Giacomo, Claudia; Modica, Maria N.; Pittalà, Valeria; Acquaviva, Rosaria; Basile, Livia; Pappalardo, Morena; Salerno, Loredana (Chemical biology & drug design, 2012)
Imidazole‐based compounds previously synthesized in our laboratory were selected and reconsidered as inhibitors of heme oxygenase‐1 obtained from the microsomal fractions of rat spleens. Most of tested compounds were good inhibitors with IC50 values in the low micromolar range. Compounds were also assayed on membrane‐free full‐length recombinant human heme oxygenase‐1; all tested compounds were unable to interact with human heme oxygenase‐1 at 100 μm concentrations with the exception of compounds 11 and 13 that inhibited the enzyme of 54% and 20%, respectively. The binding of the most active compound 11 with heme or heme‐conjugated human heme oxygenase‐1 was also examined by spectral analyses. When heme was not conjugated to human heme oxygenase‐1, compound 11 caused changes in the heme spectrum only at concentration 50‐fold (100 μm) higher than that required to inhibit rat heme oxygenase‐1; when heme was conjugated to human heme oxygenase‐1, compound 11 was able to form a heme‐compound 11 complex also at low micromolar concentrations. To obtain information on the binding mode of the tested compounds with enzyme, docking studies and pharmacophore analysis were performed. Template docking results were in agreement with experimental inhibition data and with a structure‐based pharmacophoric model. These data may be exploitable to design new OH‐1 inhibitors. Imidazole‐based compounds were evaluated as inhibitors of heme oxygenase‐1 (HO‐1); most of tested compounds were good inhibitors with IC50 values in the low micromolar range. The binding of the most active compound 11 with heme‐conjugated hHO‐1 was also examined by spectral analyses; compound 11 was able to form a heme‐compound 11 complex at low micromolar concentrations. Docking studies and pharmacophore analysis were performed to obtain informations on the binding mode; results were in agreement with experimental inhibition data.